Multimodal Integration and Phenomenal Spatiotemporal Binding: A Perspective From the Default Space Theory - Jerath, Ravinder; Beveridge, Connor (Frontiers in Integrative Neuroscience, 2019)
How does the integrated and unified conscious experience arise from the vastly distributed activities of the nervous system? How is the information from the many cones of the retina bound with information coming from the cochlea to create the association of sounds with objects in visual space? In this perspective article, we assert a novel viewpoint on the ‘binding problem’ in which we explain a metastable operation of the brain and body that may provide insight into this problem. In our view which is a component of the Default Space Theory, consciousness arises from a metastable synchronization of local computations into a global coherence by a framework of widespread slow and ultraslow oscillations coordinated by the thalamus. We reinforce a notion shared by some consciousness researchers such as Revonsuo and the Fingelkurts that a spatiotemporal matrix is the foundation of phenomenological experience and that this phenomenology is directly tied to bioelectric operations of the nervous system. Through the oscillatory binding system we describe, cognitive neuroscientists may be able to more accurately correlate bioelectric activity of the brain and body with the phenomenology of human experience.